THE POST-COLONIAL NIGERIA: AN EXPLICATORY VIEWPOINT ON SECURITY CHALLENGES AND GOVERNANCE ISSUES - Apenda, Isaac Tersoo; Ayaka, Simon Silas (African Journal of Social and Behavioural Sciences, 2024)
Postcolonial Nigeria experienced a series of internal political and security challenges due to the consistent and persistent behavioural patterns of the political elites; whose inordinate political ambitions revolved around appropriating state apparatuses against the primary interest of the led. To this effect, the country has suffered over the years in the hands of the recycled dominant political class that has produced and manipulated government institutions, thereby deepening economic and social inequalities between the elites and the masses. The study examined the factors responsible for the security challenges in Nigeria after decades of political independence. The study adopted an ex-post-facto qualitative descriptive method and relied on secondary sources of data collection. The ‘‘theory of postcolonial state’’ was employed as the main analytical construct that scientifically studies society as a whole; and considers the convergence of the unity of opposites. The paper concluded and recommended institutional revolution to end the perennial security bedevilling our dear country.